Como elaborar projetos de intervenç\~ao para a implementaç\~ao de políticas públicas? - Antônio Lassance (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– An intervention project is a proposal structured to intervene on a relevant public policy problem to offer a very specific and prototyped solution, based on a model. The project is aimed at the decision support of an organization with governance over the referred problem. The core of an intervention project is implementation, that is, the execution of actions from inputs and processes to the generation of one or more products. In some cases, these projects progress to the point of mapping processes and predicting, in detail, indicators, results and impacts to be achieved, respectively, in the short, medium and long term. But the solution chosen by a project has to meet the strategic requirement of focusing on a "node" (or bottleneck) of the problem to positively change its status. This is what justifies the project and its products. In addition to offering basic guidelines to the formulation of intervention projects with reasonable innovative potential, this working paper provides recommendations so that the implementation to be carried out by the "street level" bureaucracy maintains its adherence to the public policy strategy that originated it, avoiding what is known as the formulation of the implementation and also the mistake of developing projects that can be very successful, delivering a simple product, but do not contribute to achieve medium-term results and long-term impacts to overcome the central problem of public policy.
Keywords: D04; H11; H43; 330; intervention project; ex-ante analysis; evaluation; implementation; microeconomic public policy